STRATEGI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KOTA PEKANBARU DALAM MENINGKATKAN PENERIMAAN RETRIBUSI PENGENDALIAN MENARA TELEKOMUNIKASI - M. Ihsanul Habibi; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to identify and analyze the strategy of the Department of Transportation, Communication and Information Pekanbaru in improving sector revenue levy controlling telecommunications tower in the city of Pekanbaru. The problem in this study is not optimal retribution control telecommunication towers, while the potential revenues are not comparable with revenue realization from year to year. With targets that are considered comparable to the ability of achieving the target is not necessarily a problem that must be solved. Therefore, this study tries to analyze the strategy undertaken by the City Dishubkominfo Pekanbaru, based on the theory of strategy and policy with qualitative descriptive approach. This study shows that the strategy Dishubkominfo of the encouragement of technology in improving the reception area of the levy has been promoting the use of technology, especially in terms of information, but from the technical effectiveness has not been done. Instead of the technology market, Dishubkominfo not utilize the technology market so that the efforts of this side is felt not maximized. From the aspect of innovation strategy can be seen that Dishubkominfo Pekanbaru from the overall indicator has yet to show a systematic effort to increase local revenues from telecommunication sector levies control tower. Lastly in terms of operations strategy, there had been some activities carried out in the administrative improvement of services, improvement of the work program, forming the image of the Department. However, the program was considered not optimal for the human resources that are less qualified and absence of law enforcement committed against offenders. Internal factors such as boost the performance of leaders and external factors such as taxpayer compliance an obstacle to increased acceptance of retribution control telecom tower sector. Keywords: Strategy, Revenue, Telecommunication Tower